Halophilic Bacteria of Lunsu Produce an Array of Industrially Important Enzymes with Salt Tolerant Activity. (18th January 2016) - Gupta, Sonika; Sharma, Parul; Dev, Kamal; Sourirajan, Anuradha
Abstract : The halophilic bacterial isolates SS1, SS2, SS3, SS5, and SS8 were characterized for production of industrially important enzymes like amylase, protease, lipase, and glutaminase. Halophilic bacterial isolates SS1 and SS3 exhibited salt dependent extracellular amylase and protease activities. Both the halophilic isolates SS1 and SS3 exhibited maximum amylase and protease activities in the presence of 1.5 and 1.0 M NaCl, respectively, with the optimum pH 8 and temperature 40°C. SS2 showed maximum extracellular protease and lipase activities in the presence of 0.75 M NaCl, at optimum pH of 7, and temperature 37°C. The glutaminase activity of SS3 increased with increase in concentration of NaCl up to 2.5 M. The optimum pH and temperature for L-glutaminase activity of SS3 was 8 and 40°C, respectively. The combined hydrolytic activities of these halophilic bacterial isolates can be used for bioconversion of organic materials to useful products.